2020
DOI: 10.1177/0190272520936633
|View full text |Cite
|
Sign up to set email alerts
|

Are Birds of a Feather Praying Together? Assessing Friends’ Influence on Muslim Youths’ Religiosity in Germany

Abstract: Muslim religiosity is often portrayed as a barrier to integration into secular societies, especially in Europe. Scholars suggest that religiously segregated networks reinforce Muslims’ religiosity and religious identification, but solid evidence is scarce. Based on longitudinal German data, we examined whether friendship networks influence Muslim youths’ religiosity. Using stochastic actor-oriented models, we also assessed whether religiosity in turn relates to friendship choices. We found that higher shares o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Adolescents tend to adjust their ethnic identification toward that of their friends (Santos et al 2017), especially if these friends come from the same ethnic group (Jugert et al 2020). There also is evidence that adolescents tend to adopt the religiosity and religious behaviors of their friends (Cheadle and Schwadel 2012;Leszczensky and Pink 2020). By contrast, there is no consistent evidence that friends' mere group membership affects adolescents' social identities; neither is national identification of ethnic minority adolescents influenced by having ethnic majority friends nor is Muslim youth's religious identification influenced by having Muslim friends (Leszczensky and Pink 2020).…”
Section: Positive Peer Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents tend to adjust their ethnic identification toward that of their friends (Santos et al 2017), especially if these friends come from the same ethnic group (Jugert et al 2020). There also is evidence that adolescents tend to adopt the religiosity and religious behaviors of their friends (Cheadle and Schwadel 2012;Leszczensky and Pink 2020). By contrast, there is no consistent evidence that friends' mere group membership affects adolescents' social identities; neither is national identification of ethnic minority adolescents influenced by having ethnic majority friends nor is Muslim youth's religious identification influenced by having Muslim friends (Leszczensky and Pink 2020).…”
Section: Positive Peer Influencementioning
confidence: 99%
“…Regarding attitudes, adolescents are inclined to befriend peers with who are similar to them in general xenophobia and tolerance (van Zalk et al 2013). Research also has shown that adolescents tend to befriend peers with similar levels of religiosity (Cheadle and Schwadel 2012;Leszczensky and Pink 2020). By contrast, a recent study found no evidence that adolescents befriend peers with similar levels of homophobic attitudes (La Roi et al 2020).…”
Section: Attitude and Behavior Homophilymentioning
confidence: 99%
“…We assessed religious influence in a homogenous ethnic and religious sample with the finding that friends influenced each other with respect to both religiosity and religious coping. This research expands upon the findings of religious influence by Leszczensky and Pink (2020) who also assessed selection and influence within a sample of Muslim adolescents. Consistent with Leszczensky and Pink (2020), it appears that influence over religiousness may be particularly strong when homogenous religious samples are assessed.…”
Section: Influencementioning
confidence: 73%
“…This research expands upon the findings of religious influence by Leszczensky and Pink (2020) who also assessed selection and influence within a sample of Muslim adolescents. Consistent with Leszczensky and Pink (2020), it appears that influence over religiousness may be particularly strong when homogenous religious samples are assessed.…”
Section: Influencementioning
confidence: 73%
See 1 more Smart Citation